Hypovolemic Shock Complicating Nephrotic Syndrome in a Child - Lydia Kosnadi; Rochmanadji W.; A. G. Sumantri; Trimulyo Trimulyo; M. Rofiq Anwar (Paediatrica Indonesiana, 1988)
The fundamental abnormality in nephrotic syndrome is the structural and electrochemical changes that have been documented to occur in the glomerular basement membrane lead to proteinuria. It is the proteinuria itself which most likely causes hypoalbuminemia and associated complications such as infections, hypercoagulability and hypovolemia. Hypovolemia may cause postural hypotension, acute renal failure, circulatory collaps or sudden death. An eleven-year-old boy was referred to the Child Health Department of Dr. Kariadi Hospital Semarang with a diagnosis of corticosteroid resistant nephrotic syndrome and acute renal failure. Physical examination showed a severely ill boy with general edema, shock, hemoconcentration, hypoalbuminemia, hypercholesterolemia, massive proteinuria and disturbed renal function. The treatment consisted of infusion of dextrose 10% followed by human plasma and furosemide to restore plasma volume and enhance urine production. Two days later he was in better condition, normovolemia, slight edema, good diuresis, but his blood pressure increased, and ophtalmologic examination supported the diagnosis of grade I hypertensive retinopathy. Intravenous clonidine and furosemide were given and were very effective. Kidney biopsy revealed minimal lesion with slight proliferation.